Adaptasi Masyarakat Dalam Menghadapi Bencana Banjir Tahunan di Desa Kuala Terusan Kecamatan Pangkalan Kerinci Kabupaten Pelelawan - Febry Novryaldi Nababan; Rina Susanti (Peneliti.net, 2023)
This study intends to explain how the Community Adapts in Facing the Annual Flood Disaster that occurred in Kuala Terusan Village. Flooding is a phenomenon that occurs annually in Kuala Terusan Village which makes people adapt to changes in the surrounding environment that occur. The theory used is the theory of adaptation with the theory of supporting social action. This research is a qualitative type with data collection techniques in the research in the form of purposive sampling where the number of informants is 6 informants with the criteria, the Kuala Terusan Village Community has experienced flooding for at least 4 years, the Kuala Terusan Village Community has felt the direct impact of flooding, which is then analyzed using supporting theory. The results of field research show that the floods that occurred in Kuala Terusan Village had an impact felt by residents, both positive and negative impacts. change in terms of economic, social, structural, and cultural.